Taking stock of cost-effectiveness analysis of healthcare in China - Thomas Butt; Gordon G Liu; David D Kim; Peter J Neumann (BMJ Global Health)
Introduction Cost-effectiveness analysis (CEA) is playing an increasingly important role in informing healthcare decision-making in China. This study aims to review the published literature on CEA in mainland China and describe its characteristics and evolution. We provide recommendations on the future direction of CEA as a methodology and as a tool to support healthcare decision-making in China.Methods English-language cost-per-quality-adjusted life-year (QALY) and cost-per-disability-adjusted life-year (DALY) publications relating to mainland China were reviewed using the Tufts Medical Center Cost-Effectiveness Analysis Registry and Global Health Cost-Effectiveness Analysis Registry through 2017. Study features were summarised using descriptive statistics. Changes in study methodology over time were analysed by trend test, and study characteristics influencing the incremental cost-effectiveness ratio (ICER) of cost-per-QALY studies were investigated using logistic regression.Results 170 studies were identified reporting CEA for mainland China (cost/QALY=125, cost/DALY=45) since 1998. The number and quality of studies has increased over the past two decades, with significantly more cost-per-QALY studies compared with cost-per-DALY studies (p<0.0001) and more studies with authors affiliated with Chinese institutions (p=0.0002). The average quality score was 5.04 out of 7 for cost-per-QALY and 4.70 for cost-per-DALY studies based on Registry reviewers’ subjective assessment of overall quality (methods, assumptions and reporting practices). The median ICER reported for interventions for oncology patients was higher (US$26 694 per QALY) than the median ICER reported for all interventions (US$11 503 per QALY). Oncology interventions were associated with the likelihood of reporting higher ICERs than the median ICER (p=0.003).Conclusion The number of English-language published CEA studies relating to China has grown rapidly over the past 20 years. In terms of quality, the China studies compare favourably with international studies, although they remain a small proportion of studies globally.